Genomic data of leptospira interrogans hp358 isolated from rodent captured from the human leptospirosis suspected areas of Selangor state, Malaysia - Noraini Philip; Jaeyres Jani; Nurul Natasya Azhari; Zamberi Sekawi; Vasantha Kumari Neela (Elsevier Inc., 2021)
The data provided in this article is the genomic sequence of new Leptospira isolate, Leptospira interrogans strain HP358 ( L. interrogans HP358) isolated from rodent, Sundamys muel- leri (S. muelleri) , captured from the human leptospirosis sus- pected area, in forest environment, Hulu Perdik, Selangor. The kidney of the rodent was cultured, and the genomic DNA of pure Leptospira isolate was extracted and sequenced. The de novo assembly of genome generated 118 contigs with N50 of 133,176bp. The genome size of the L. interrogans HP358 was determined with a length of 4,808,724 and 35.01% G + C content with 229 subsystems, 5236 coding sequences and 39 RNAs. The whole genome shotgun project has been de- posited in NCBI GenBank under the accession number JAF- CYY0 0 0 0 0 0 0 0 0.1.